The need for location-specific biometeorological indexes in Taiwan - Wong, Ho Ting; Nguyen, Tuan Duong (Frontiers in Public Health, 2022)
Objective: As most of the biometeorological indexes available were developed decades ago in western countries, the benefit of using these indexes to study the effect of weather on human health in modern eastern countries is questionable. This study has aimed to confirm further the effectiveness of applying biometeorological indexes when analyzing daily emergency ambulance services (EAS) demand in Taipei. Methods: More than 370,000 EAS usage records were analyzed in this study. The records were first transformed into different time-series data by age, gender, triage level, and case nature (trauma/non-trauma) in order to represent different kinds of daily EAS demand. They were then regressed on biometeorological indexes (Apparent Temperature, AT and Net Effective Temperature, NET), and the indexes’ additional descriptive power to describe the daily EAS demand over traditional weather factors was assessed. Results: No significant difference was observed in the descriptive powers on daily EAS demand of the biometeorological indexes and traditional weather factors. The largest improvement on the regression models’ adjusted-R2 using NET and AT was only 0.008. Conclusion: It may not be a good idea to make direct use of the biometeorological indexes developed in western countries decades ago. Taiwan should have a tailor-made biometeorological index for a better representation of its unique situation.